Taking a Precautionary Approach to Climate Mitigation Measures in the Southern Ocean - Mayo-Ramsay, JP (Faculty of Law, UTAS, 2008)
The Southern Ocean waters around Antarctica provide a uniqueenvironment in a complex marine ecosystem. One of theconsequences of global warming is the rise in ocean temperaturefrom the increased absorption of anthropogenic carbon dioxide(CO:) by the oceans, which may have an impact on thebiodiversity within this system.' For over ten years fertilising theocean with iron has been trailed in high nutrient low chlorophyll(HNLC) areas of the Southern Ocean in order to stimulatephytoplankton growth and the subsequent drawdown of CO: intothe ocean. Before ocean fertilisation can, however, be safelyconsidered as a viable mitigating measure for climate change thereneeds to be reliable measures in place to ensure there is noirreversible damage to the marine environment. The precautionaryprinciple is one tool that has been used as a form of customary lawto protect the environment in light of scientific uncertainty.Application of the principle, does however, require scientists andlaw-makers to work closely together in order to develop suitableguidelines along with an ecosystem monitoring program toeffectively detect and manage impact on species before there isirreversible damage to the Antarctic marine ecosystem.